Implementation of the Rahn and Qardh Contracts in Sharia Gold Pawn Products at the Bandar Lampung Branch of Sharia Pawnshop - Nur Khalifah Putri; Nina Ramadhani Wulandari; Mawardi (ProBisnis : Jurnal Manajemen, 2023)
Pawnshop is the only formal institution based on banking law that carries out financing in the form of lending on the basis of pawn law. The purpose of this research is to determine the implementation of the rahn agreement at the Bandar Lampung Lampung Branch of the Sharia Pawnshop, to determine the suitability of the implementation of the rahn agreement at the Bandar Lampung Lampung Branch of the Sharia Pawnshop with the DSN MUI fatwa No: 25/DSN-MUI/III/2002 concerning rahn, DSN fatwa MUI No: 26/DSN-MUI/III/2002 concerning gold rahn, and DSN MUI fatwa No: 92/DSN-MUI/IV/2014 concerning financing accompanied by rahn. The research carried out was field research using qualitative methods. The results of the research show that the gold pawn product at the Bandar Lampung Lampung Branch of the Sharia Pawnshop is a unique unit of rahn and qardh contracts and regarding the implementation of the rahn contract at the Sharia Pawnshop it is in accordance with the DSN MUI fatwa No: 25/DSN-MUI/ III/2002 about Rahn. However, it is not in accordance with DSN MUI fatwa No: 26/DSN-MUI/III/2002 concerning gold rahn and DSN MUI fatwa No: 92/DSN-MUI/IV/2014 concerning financing accompanied by rahn.